RELEVANSI KAMPUS MERDEKA TERHADAP KOMPETENSI GURU ERA 4.0 DALAM PERSPEKTIF EXPERIENTIAL LEARNING THEORY - Sigit Priatmoko; Nilna Iqbal Dzakiyyah (Universitas Islam Lamongan, 2020)
The presence of the Kampus Merdeka policy reaps the pros and cons of various circles. Criticisms were raised against administrative obstacles, differences in standards between tertiary institutions, and graduate scientific specifications. This study wants to analyze the relevance of this policy to the competence of teachers in the era of the industrial revolution 4.0, which is reviewed from the perspective of Experiential Learning Theory (ELT). The method used in this study is a literature review. Data was obtained from various sources, especially the official website of the Ministry of Education and Culture, official website, and other relevant scientific articles and literature. The analysis shows that there is relevance between Kempus Merdeka with the competence of teachers in the 4.0 era and ELT. The policy aspects of the Merdeka Campus are in harmony with ELT and are able to support the achievement of teacher competencies in the 4.0 revolution era. the relevance appears in aspects; holistic, integrative, scientific, contextual, thematic, effective, collaborative, and student-centered.